The First Saudi Study Investigating the Plasmid-borne Aminoglycoside and Sulfonamide Resistance among Acinetobacter baumannii Clinical Isolates Genotyped by RAPD-PCR: the Declaration of a Novel Allelic Variant Called aac(6ʹ)-SL and Three Novel Mutations in the sul1 Gene in the Acinetobacter Plasmid (s) - El-Badawy MF (Dove Medical Press, 2021)
Mohamed F El-Badawy,1 Fatma I Abou-Elazm,2 Mohamed S Omar,3 Mostafa E El-Naggar,4 Ibrahim A Maghrabi5 1Department of Microbiology and Immunology, Faculty of Pharmacy, University of Sadat City, Sadat City, Menoufia, 32897, Egypt; 2Department of Microbiology and Immunology, Faculty of Pharmacy, Misr University for Science and Technology, 6th of October City, Egypt; 3Department of Chemistry, Faculty of Science, Benha University, Benha, 13508, Egypt; 4Department of Pharmacology and Toxicology, Faculty of Pharmacy, University of Sadat City, Sadat City, Menoufia, 32897, Egypt; 5Department of Clinical Pharmacy, College of Pharmacy, Taif University, Taif, 21974, Saudi ArabiaCorrespondence: Mohamed F El-BadawyDepartment of Microbiology and Immunology, Faculty of Pharmacy, University of Sadat City, Sadat City, Menoufia, 32897 EgyptTel +20 103-205-9964Email Mohamed.Elbadawy@fop.usc.edu.egBackground: Acinetobacter baumannii (A. baumannii) is one of the most important nosocomial pathogens responsible for a wide range of infections.Aim: This study aimed to investigate the existence of the plasmidic genes encoding for aminoglycoside modifying enzymes (AMEs), 16S rRNA methyltransferases (RMT), and the altered dihydropetroate synthase (DHPS) encoded by the sul1 gene among A. baumannii clinical isolates collected from Taif, Kingdom of Saudi Arabia (KSA). The mutations in aac(6ʹ)-Ib and sul1 genes were also investigated.Methods: Forty A. baumannii clinical isolates were investigated for their susceptibility to ten antibiotics. The plasmid DNA was extracted and screened for nine genes encoding for aminoglycoside resistance in addition to the sul1 gene. The clonal relatedness was determined by random amplified polymorphic DNA (RAPD)-PCR. Mutation in aac(6ʹ)-Ib and the sul1 genes were detected by capillary electrophoresis sequencing (CES).Results: All isolates were A. baumannii in which 42.5% of them exhibited a high level of aminoglycoside resistance (HLAR). The most prevalent AMEs and RMT encoding genes were aph(3ʹ)-VI, the two aac(6ʹ) gene variants [aac(6ʹ)-Ib and aac(6ʹ)-SL], ant(3ʹʹ)-I, and armA in which 90%, 87.5%, 85%, and 45% of isolates tested positive, respectively. The other investigated aminoglycoside resistant encoding genes, namely aac(3)-II, aac(6ʹ)-II, and rmtB, were not detected. Only 15% of isolates harbored the sul1 gene. RAPD-PCR classified the 40 isolates into three clusters in which cluster II was the main cluster. DNA sequencing revealed that 34.29% (12/35) of isolates tested positive for aac(6ʹ)-Ib were found to harbor a common missense mutation in position 102 indicating a novel allelic variant named aac(6ʹ)-SL. Also, DNA sequencing revealed three missense mutations in the sul1 gene.Conclusion: This is the first Saudi study to investigate the plasmid borne aminoglycoside and sulfonamide resistance genes among A. baumannii clinical isolates. A novel allelic variant for aac(6ʹ)-Ib was detected in addition to novel mutations in the sul1 gene.Keywords: AMEs, armA, RAPD-PCR, A. baumannii, 16S rRNA